Preparation of Silica Nano-Particles by Sol-Gel Method and Its Characterization - Bhatt, Neha; Mishra, Abhilasha; Goswami, Rekha; Prasad, Brijesh (Journal of Graphic Era University, 2021)
Nano silica (SiO2) has an extensive range of products from manufacturing to scientific. The Sol-gel technique in the field of material science is receiving worldwide interest because of its versatility for synthesizing silica nanoparticles. It provides a controlled composition of organic/inorganic hybrid material because of its unique and low-cost processing. The silica nanoparticles were prepared by the sol-gel method via two different routes first is a basecatalyzed hydrolysis reaction and the second is an acid-catalyzed hydrolysis reaction. The prepared silica nanoparticles were characterized by techniques Particle size analysis, Zeta potential, Fourier transform Infrared spectroscopy (FTIR), and X-Ray diffraction spectroscopy (XRD). Particle size analysis showed the nano range of particle and zeta potential proves the stability of prepared sols. Observed peaks from IR spectra are confirming the presence of a silica network. The amorphous silica was verified by the absence of sharp peaks and the presence of a broad peak at a 2 angle of 23.8 for the XRD analysis structure in the produced NPs.